Identification and Prioritization of Canadian Society of Nephrology Clinical Practice Guideline Topics With Multidisciplinary Stakeholders and People Living With Kidney Disease: A Clinical Research Protocol - Brigitte H. Baragar; Melissa Schorr; Nancy Verdin; Tania Woodlock; David A. Clark; Gregory L. Hundemer; Anna Mathew; Reem A. Mustafa; Krista S. Ryz; Tyrone G. Harrison (Canadian Journal of Kidney Health and Disease, 2023)
Background: Despite efforts to provide evidence-based care for people living with kidney disease, health care provider goals and priorities are often misaligned with those of individuals with lived experience of disease. Coupled with competing interests of time, resources, and an abundance of suitable guideline topics, identifying and prioritizing areas of focus for the Canadian nephrology community with a patient-oriented perspective is necessary and important. Similar priority-setting exercises have been undertaken to establish research priorities for kidney disease and to standardize outcomes for kidney disease research and clinical care; however, research priorities are distinct from priorities for guideline development. Inclusion of people living with health conditions in the selection and prioritization of guideline topics is suggested by patient engagement frameworks, though the process to operationalizing this is variable. We propose that the Canadian Society of Nephrology Clinical Practice Guideline Committee (CSN CPGC) takes the opportunity at this juncture to incorporate evidence-based prioritization exercises with involvement of people living with kidney disease and their caregivers to inform future guideline activities. In this protocol, we describe our planned research methods to address this. Objective: To establish consensus-based guideline topic priorities for the CSN CPGC using a modified Delphi survey with involvement of multidisciplinary stakeholders, including people living with kidney disease and their caregivers. Study design: Protocol for a Modified Delphi Survey. Setting: Pilot-tested surveys will be distributed via email and conducted using the online platform SurveyMonkey, in both French and English. Participants: We will establish a group of multidisciplinary clinical and research stakeholders (both within and outside CSN membership) from Canada, in addition to people living with kidney disease and/or their caregivers. Methods: A comprehensive literature search will be conducted to generate an initial list of guideline topics, which will be organized into three main categories: (1) International nephrology-focused guidelines that may require Canadian commentary, (2) Non-nephrology specific guidelines from Canada that may require CSN commentary, and (3) Novel topics for guideline development. Participants will engage in a multi-round Modified Delphi Survey to prioritize a set of “important guideline topics.” Measures: Consensus will be reached for an item based on both median score on the Likert-type scale (≥ 7) and the percentage agreement (≥ 75%); the Delphi process will be complete when consensus is reached on each item. Guideline topics will then be given a priority score calculated from the total Likert ratings across participants, adjusted for the number of participants. Limitations: Potential limitations include participant response rates and compliance to survey completion. Conclusions: We propose to incorporate evidence-based prioritization exercises with the engagement of people living with kidney disease and their caregivers to establish consensus-based guideline topics and inform future guidelines activities of the CSN CPGC.